A Diversity of Sacramental Ordinations in an Evolving World and Church - McManus, Kathleen Anne (Concilium, 2025)
Who can validly administer the Sacrament of Anointing of the Sick? From the starting point of the evolutionary nature of the development of doctrine illustrated in the history of Anointing, this essay gestures towards a public ecclesial sanctioning of the hidden sacramental ministries of women and laity through a "diversity of sacramental ordinations."